Design and analysis of Micro-Cantilever based Biosensor for Swine flu Detection - M.G.G. Jithendra Prasad; Shameem Syed (Institute of Advanced Engineering and Science, 2016)
Swine flu which comes under the category of influenza is caused by N1H1 virus. This Disease in 2009 was termed as pandemic by WHO (World Health Organisation). It was fast spreading almost all over the world then. It is same as normal Flu and can be prevented by flu shots/vaccines. The real importance of the disease is because , it may cause serious health conditions like Pneumonia, Respiratory asthma, bronchitis different types of mucus line cancers ,unlike normal flu. Sometimes human life can be endangered by post effects of Swine flu. According to a study Infant mortality is because due to lack of detection of diseases. Thus Detection of Swine flu virus, which is cause for infant mortality is important. This can be done using the most trusted form by using MEMS. In this paper the Micro-Cantilever is used as the sensing unit. Using COMSOL 4.3b, we designed rectangular cantilever and also a rectangle with a hole punched forming SCR (Stress Concentration Region) concept, analysed and optimized.